Fertilizer demonstration, agricultural performance, and food security of smallholder farmers: Empirical evidence from Nepal - Dr. Ganesh Thapa; Dr. Dyutiman Choudhary; Dr. Naba Raj Pandit; Prabin Dongol (World Development Sustainability)
Low agricultural productivity in developing countries is attributed towards the low and inefficient use of chemical fertilizers. Fertilizer demonstrations have been a useful extension tool to change the farmers’ awareness and perception towards the right use of fertilizer application. About 180 fertilizer demonstrations (demos) on rice and maize were conducted in farmers field in 2017 and 2018 in western Nepal to promote the 4R nutrient stewardship that incorporates the right fertilizer source at the right rate, at the right time, and in the right place including the best management practices. Household surveys were conducted in 2018 and 2019 after the successful completion of fertilizer demonstrations. We assess the determinants of farmers’ participation in fertilizer demos and estimates its impact on fertilizer adoption, agricultural performance, and food security in Nepal. Our doubly robust impact evaluation approach accounts for non-random patterns of use of hybrid varieties, higher seed replacement rates, and proximity to the demo plots (within one kilometer of demo site). Farmers who participated in demos have higher fertilizer adoption rate and were more likely to use balanced fertilizers (nitrogen, phosphorus, and potassium). Results indicate that the demo participation would lead to significantly increase rice productivity, household maize consumption and agriculture commercialization. Agriculture policy should underscore in organizing the demos to promote the best nutrient management practices and sustain agricultural production and ensure food security. However, such demos should also be located near to the poor, who use less advanced agronomic practices, or in other locations to those traditionally chosen for demonstration plots to ensure the productivity gains by poor and marginal households.